Defining the language of the software application using the vocabulary of the domain - Antonelli, Rubén Leandro (2022)
Requirements engineering is one the most critical stages in software development. If the requirements are not correct the software development team will produce an artifact that will not satisfy the needs, wishes and expectations of the client. Requirements (and knowledge in general) are spread among many stakeholders. Natural language is widely used since it is an adequate tool considering non-technical stakeholder. Nevertheless communication problems arise with the use of natural language. The software development team members need to learn about the application domain and this process of learning means focusing on the features to be included in the software application, while leaving apart the elements out of the boundaries of the application. This process is not easy when people face a new application domain. Thus, this paper proposes an approach to define the software application language from a vocabulary of the application domain.